The Effect on Nonmember Banks of the Imposition of Member Bank Reserve Requirements–With and Without Federal Reserve Services - Goldberg, Lawrence G.; Rose, John T. (Journal of Finance, 1976)
Lawrence G. Goldberg, John T. Rose, The Effect on Nonmember Banks of the Imposition of Member Bank Reserve Requirements–With and Without Federal Reserve Services, The Journal of Finance, Vol. 31, No. 5 (Dec., 1976), pp. 1457-1469